The Trans-autostimulatory Activity of Rad27 Suppresses dna2 Defects in Okazaki Fragment Processing - Munashingha, Palinda Ruvan (American Society for Biochemistry and Molecular Biology, 2012)
Dna2 and Rad27 (yeast Fen1) are the two endonucleases critical for Okazaki fragment processing during lagging strand DNA synthesis that have been shown to interact genetically and physically. In this study, we addressed the functional consequences of these interactions by examining whether purified Rad27 of Saccharomyces cerevisiae affects the enzymatic activity of Dna2 and vice versa. For this purpose, we constructed Rad27DA (catalytically defective enzyme with an Asp to Ala substitution at amino acid 179) and found that it significantly stimulated the endonuclease activity of wild type Dna2, but failed to do so with Dna2Δ405N that lacks the N-terminal 405 amino acids. This was an unexpected finding because dna2Δ405N cells were still partially suppressed by overexpression of rad27DA in vivo. Further analyses revealed that Rad27 is a trans-autostimulatory enzyme, providing an explanation why overexpression of Rad27, regardless of its catalytic activity, suppressed dna2 mutants as long as an endogenous wild type Rad27 is available. We found that the C-terminal 16-amino acid fragment of Rad27, a highly polybasic region due to the presence of multiple positively charged lysine and arginine residues, was sufficient and necessary for the stimulation of both Rad27 and Dna2. Our findings provide further insight into how Dna2 and Rad27 jointly affect the processing of Okazaki fragments in eukaryotes.